John Law and John Keynes - Wilson, Edwin B. (Quarterly Journal of Economics, 1948)
Wicksteed on the scope and method of political economy, 381. — Early theorizing about the influence of monetary conditions on the activity of trade, 383. — Characteristics of Keynes' thinking, 386. — Law's Money and Trade Considered, 388. — Adam Smith's misinterpretation, 389. — Origins of the Mississippi Scheme, 391. — Difficulty of controlling social developments, 392. — Parallel between Law and Keynes, 393. — Need for further study of monetary theory, 395.